COMPARISON OF SENSORY CHARACTERISTICS AND BIOCHEMICAL PARAMETERS IN COMMERCIAL FROZEN PRAWN - LAKSHMANAN, P T; THOMAS, FRANCIS; VARMA, P R.G; MATHEN, CYRIAC (Fishery Technology, 2017)
Commercial samples of frozen shrimp of different styles of presentation and size grades were tested for sensory, physical (cooked yield and pH) and biochemical characteristics (moisture, total nitrogen, water extractable nitrogen, nonprotein nitrogen, alpha amino nitrogen, total volatile nitrogen and trimethylamine nitrogen). The test results are compared and correlated. The order of preference of the samples wereHL > PUD > P & D. There was significant correlation between sensory score of cooked sample and WEN, NPN and co - NH2-Nvalues. TVN and TMA-N did not exhibit any correlation with sensory score. It is inferred that in quality measurement of frozen shrimps of commerce the quantity of water soluable components and the total dry matter can be used to support the sensory test results